2021
DOI: 10.1071/es20005
|View full text |Cite
|
Sign up to set email alerts
|

Weather systems and extreme rainfall generation in the 2019 north Queensland floods compared with historical north Queensland record floods

Abstract: Earlier papers have addressed floods from warm-air advection (WAA) in southeast Australia and around the globe, and extreme rainfall in US hurricanes and Australian tropical cyclones (TCs). This is the first paper to address the WAA phenomena in causing monsoon and TC floods and in TC-like systems which develop over the interior of northern Australia. The inland events help explain Australia’s worst tropical flooding disaster in 1916. A disastrous series of floods during late January and early February 2019 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…While the Temperature Humidity Index has been successfully used to quantify the heat stress in Bos taurus (cooler climate) and Bos indicus (warmer climate) cattle breeds 5 , there is a currently a knowledge gap in our understanding of the effect of cold stress on northern Australia cattle 6 . Less is known about cattle comfort during the Australian summer months (December to February) when temperatures can rapidly drop when a monsoon depression or tropical cyclone makes landfall, as was the case in February 2019 over the Gulf 7 . Previous studies have predominantly focused on beef cattle in North America where animals have access to sheltered pens for protection from sub-zero temperatures 8 , 9 or have focused on the detrimental impacts of warmer temperatures on northern Australia forage production and animal stress 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the Temperature Humidity Index has been successfully used to quantify the heat stress in Bos taurus (cooler climate) and Bos indicus (warmer climate) cattle breeds 5 , there is a currently a knowledge gap in our understanding of the effect of cold stress on northern Australia cattle 6 . Less is known about cattle comfort during the Australian summer months (December to February) when temperatures can rapidly drop when a monsoon depression or tropical cyclone makes landfall, as was the case in February 2019 over the Gulf 7 . Previous studies have predominantly focused on beef cattle in North America where animals have access to sheltered pens for protection from sub-zero temperatures 8 , 9 or have focused on the detrimental impacts of warmer temperatures on northern Australia forage production and animal stress 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The weather system responsible for the extreme compound event was a quasi-stationary tropical low, described as a warm-air advection event (anticyclonic turning of winds with height) with cooler mid-level air drawn in from higher latitudes 7 . In the lead up to the tropical low deepening (26-27 January), a shallow inland trough stretched across tropical northern Australia, linking tropical cyclone Riley (off the northwest coast) and a tropical low over Cape York Peninsula 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index is a modification of the AUSSM index proposed in Yim et al [25] based on the climatological monsoon depression in Figure 2a, where the westerlies appear in the north and easterlies in the south. After comparing the difference between the wind shear and the westerly [6,7,26] monsoon indices, we found that the wind shear index has the merit of showing clear seasonal contrast separated by the onset date and the cyclonic structure of the clockwise (cyclonic) monsoon depression over the interior of northern Australia [27]. The subseasonal variations of these indices in summer 2018/19 can be easily identified in Figure 2c,d. A strong westerly surge occurred in late January and lasted until mid-February.…”
Section: Australia Monsoon Troughmentioning
confidence: 89%
“…Therefore, the strong ER influence in 2019 seems to be unusual. The strong enhancement by other factors, such as the Warm Air Advection (WAA) described in Callaghan [27], can be important. Further research in this direction is desperately needed to find enough evidence to support the hypothesis.…”
Section: Spre Ranked Rainfall Amountmentioning
confidence: 99%